182k views
5 votes
3. (07.09)Given the following functions f(x) and g(x), solve(-3) and select the correct answer below: (1point)f(x) = 6x + 8=g(x) = x - 2O-2NI2.0INO 2

3. (07.09)Given the following functions f(x) and g(x), solve(-3) and select the correct-example-1

1 Answer

3 votes

Knowing the functions f(x) and g(x), we can express (f/g)(x) as:


(f)/(g)(x)=(f(x))/(g(x))=(6x+8)/(x-2)

we then can calculate (f/g)(-3) by replacing x with -3:


\begin{gathered} (f)/(g)(-3)=(6(-3)+8)/(-3-2) \\ (f)/(g)(-3)=(-18+8)/(-5) \\ (f)/(g)(-3)=(-10)/(-5) \\ (f)/(g)(-3)=2 \end{gathered}

Answer: (f/g)(-3) = 2

User Ryan Parman
by
4.4k points